2013
DOI: 10.1097/yic.0b013e32835d735d
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular mechanisms of SSRI drugs and their benefits and risks in ischemic heart disease and heart failure

Abstract: Depression and heart disease are commonly comorbid. Selective serotonin reuptake inhibitors (SSRIs) are commonly used to treat depression. In March 2011, we carried out a 15-year search of PubMed for preclinical and clinical publications related to SSRIs and ischemic heart disease (IHD) or congestive heart failure (CHF). We identify and discuss a number of mechanisms by which SSRIs may influence cardiovascular functioning and health outcomes in patients with heart disease; many of the mechanisms that we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…There already are clinically and translationally important data concerning paroxetine and HF. HF patients are often depressed, and trials have shown that paroxetine along with other SSRIs can be used effectively to treat depression in these patients (32)(33)(34). Although this therapy certainly improves mental outlook and data have shown improvement in patient outcomes and quality of life (32)(33)(34), specific improvements in cardiac function have not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…There already are clinically and translationally important data concerning paroxetine and HF. HF patients are often depressed, and trials have shown that paroxetine along with other SSRIs can be used effectively to treat depression in these patients (32)(33)(34). Although this therapy certainly improves mental outlook and data have shown improvement in patient outcomes and quality of life (32)(33)(34), specific improvements in cardiac function have not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…There are several mechanisms through which SSRIs may improve heart function particularly in depression. For example they reduce heart rate, increase heart rate variability (55; 56; 58; this report), inhibit serotonin-mediated and collagen-mediated platelet aggregation, reduce inflammatory mediator levels, and improve endothelial function (59). …”
Section: Discussionmentioning
confidence: 99%
“…SSRIs are the drug of choice for anxiety and depression, which may be ideally suited to hypercholesterolemic patients. These medicines may also decrease cardiovascular risks and improve clinical cardiovascular end points through several mechanisms 20. However, SSRIs are commonly associated with pharmacokinetic drug interactions, and many of these inhibit the metabolism of other drugs, thereby raising the blood levels of many coadministered drugs.…”
Section: Discussionmentioning
confidence: 99%